Citizen Lawsuit Atas Pengawasan Terhadap Kebijakan Pemerintah - Aliffia Intan Maharani; Fildzah Hanifati Nadhilah (Peneliti.net, 2022)
The occurrence of law violations committed by state administrators in implementing several policies resulting in losses for citizens has encouraged the public to take part in efforts to resolve friction as well as participate in law enforcement. Citizens can file lawsuits in court in terms of demanding fulfillment of responsibilities to the state for the benefit and/or public interest to protect the interests of citizens who feel aggrieved. Citizen Lawsuit is one of the efforts by citizens that can be carried out in filing the lawsuit. The Citizen Lawsuit mechanism has not specifically been regulated in laws and regulations. At this writing, the author will examine and elaborate further regarding citizen oversight of government policies and also the Citizen Lawsuit mechanism in Indonesia as control over the supervision of government actions and also what is used as an assessment point for unlawful behavior by state administators who are filed in public lawsuits or citizen (Citizen Lawsuit)